2017
DOI: 10.1039/c6fo01845a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soybean protein on blood pressure in postmenopausal women: a meta-analysis of randomized controlled trials

Abstract: The effect of soybean protein on blood pressure (BP) in postmenopausal women is controversial, so we aimed to conduct a systematic review and a meta-analysis of published randomized controlled trials (RCTs) to investigate whether supplementation with soy protein improves their blood pressure. PubMed and Embase were searched up to February 2016. Weighted mean differences were calculated for net changes in BP by using fixed-effect or random-effect models. Subgroup and meta-regression analyses were performed to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…Subgroup analyses indicated that the significant reduction in BP occurred only among individuals with hypertension and in younger ages (less than 60 years of age). More recently, Kou et al conducted a meta-analysis of 12 RCTs (1,551 participants) of soy protein on BP among post-menopausal women [ 145 ]. They concluded that ingestion of soy protein significantly reduced systolic BP by 3.03 mmHg and diastolic BP by 0.71 mmHg..…”
Section: Chd Atherosclerosis Arterial Stiffness and CV Risk Factormentioning
confidence: 99%
“…Subgroup analyses indicated that the significant reduction in BP occurred only among individuals with hypertension and in younger ages (less than 60 years of age). More recently, Kou et al conducted a meta-analysis of 12 RCTs (1,551 participants) of soy protein on BP among post-menopausal women [ 145 ]. They concluded that ingestion of soy protein significantly reduced systolic BP by 3.03 mmHg and diastolic BP by 0.71 mmHg..…”
Section: Chd Atherosclerosis Arterial Stiffness and CV Risk Factormentioning
confidence: 99%
“…A Bayesian meta‐analysis of RCTs indicates that exposure to isoflavones can modestly, but significantly, improve endothelial function as measured by flow‐mediated dilation . In addition, soy protein intake more than 25 g per day or isoflavone intake more than 100 mg per day has blood pressure‐lowering effects in postmenopausal women . Moreover, soy proteins exert beneficial effects on the serum lipid profile (LDL‐cholesterol, HDL‐cholesterol, triglyceride and total cholesterol), and the effect was stronger in hypercholesterolaemic subjects .…”
Section: Resultsmentioning
confidence: 99%
“…For example, in the last five years alone five synthetic reviews have observed benefits for cardiovascular disease mortality, improved lipid profiles, markers of inflammation and glycaemic control, especially amongst participants with poor health i.e., hypercholesterolemia at baseline [ 18 , 19 , 24 , 25 , 26 ]. Of the plant-based proteins, the evidence for soy protein appears to be particularly strong, with potential benefits for blood pressure and low-density lipoprotein reduction [ 20 , 23 ] and gains in strength and lean body mass [ 21 ].…”
Section: Plant-derived Proteinsmentioning
confidence: 99%